Hubungan tingkat pendidikan ibu dan pengetahuan ibu tentang 1000 HPK dengan kejadian stunting pada balita 0-59 bulan - Nurlaili Nurlaili; Alkhair Alkhair; Hairunnisah Hairunnisah; Nur Husnul Khatimah (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Stunting is a major public health issue, with prevalence rates remaining above the WHO critical threshold. At the family level, a mother's formal education and accurate understanding of the first 1000 days of life period are key pillars determining a child's nutritional status and growth. Purpose: To analyze the relationship between maternal education levels and knowledge regarding the first 1000 days of life period and the incidence of stunting in children aged 0-59 months. Method: This observational analytic study, utilizing a case-control design, was conducted in the working area of ​​the Rasanae Timur Community Health Center, Bima City, between February and March 2026. The study sample consisted of 89 mothers with children aged 0–59 months. Primary data were collected using a structured questionnaire regarding education and knowledge concerning the